(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The critical revision was done for the collection of the myxomycetes, made by Prof. І.О. Dudka during 05–06.05.2006, 16.08.2006 and 13–14.09.2006 in the Ugolksko-Shyrokoluzhansky, Chornohirsky and Marmarosky massifs of the Carpathian biosphere reserve. Collection is kept in the mycological section of the herbarium of H.S. Skovoroda Kharkiv National Pedagogical University, under numbers CWP (Myc) 3110–3137. The material of the collection was previously used in the preparation of the publication about the virgin beech forests of the Ukrainian Carpathians. Seventeen species of myxomycetes from 11 genera, 7 families and 4 orders of the class Myxomycetes were revealed: Ceratiomyxa fruticulosa (O.F. Müll.) T. Macbr., Diachea lencopodia (Bull.) Rostaf., Didymium clavus (Alb. et Schwein.) Rabenh., Fuligo candida Pers. sensu B. Ing, F. septica (L.) F.H. Wigg. f. flava (Pers.) Y.Yamam., Hemitrichia cf. clavata (Pers.) Rostaf., Licea minima Fr., Lycogala epidendrum (L.) Fr. sensu B. Ing, L. terrestre Fr. sensu B. Ing, Metatrichia floriformis (Schwein.) Nann.-Bremek., M. vesparia (Batsch) Nann.-Bremek. ex G.W. Martin et Alexop., Stemonitopsis typhina (F.H. Wigg.) Nann.-Bremek., Trichia affinis Rostaf., T. crateriformis G.W. Martin, T. varia (Pers. ex J.F. Gmel.) Pers., T. persimilis P. Karst. and Tubifera cf. ferruginosa (Batsch) J.F. Gmel. The identification оf two specimens, provided the publication of the 2011, was revised: “Fuligo intermedia” was re-identified as F. candida, while “Physarum robustim” appeared to be Didymium clavus. Thus, the previously stated assertion about the presence of these two species in the Ukrainian Carpathians was premature. On the contrary, T. decipiens var. olivacea, which was previously described as the variety of T. decipiens, new to the Ukrainian Carpathians, is currently considered as the independent species, T. crateriformis G.W. Martin, which appeared to be new for the region.